Nutritional abrogation of photoimmunosuppression: in vivo investigations. Issue 2 (2nd January 2014) - Pilkington, Suzanne M.; Gibbs, Neil K.; Friedmann, Peter S.; Rhodes, Lesley E.
Summary Skin cancer is a major public health concern, and the primary aetiological factor in the majority of skin cancers is ultraviolet radiation (UVR) exposure. UVR not only induces potentially mutagenic DNA damage but also suppresses cell‐mediated immunity (CMI), allowing cancerous cells to escape destruction and progress to tumours. A considerable proportion of an individual's annual sun exposure is obtained outside the vacation period when topical and physical measures for photoprotection are irregularly used. Certain nutrients could provide an adjunctive protective role, and evidence is accruing from experimental studies to support their use in abrogation of photoimmunosuppression. Moreover, developments in clinical research methods to evaluate impact of solar‐simulated radiation on cutaneous CMI allow the immune protective potential of nutritional agents to be examined in humans in vivo. This article summarises the mediation of CMI and its suppression by UVR, evaluates the methodology for quantitative assessment in vivo, reviews the human studies reported on nutritional abrogation of photoimmunosuppression including recent randomized controlled trials and discusses the mechanisms of photoprotection by the nutrients. This includes, in addition to antioxidants, novel studies of omega‐3 polyunsaturated fatty acids and nicotinamide.